Analisis Determinan Pembayaran Tunggalan Pajak pada Kantor Pelayanan Pajak Medan Belawan - Teuku Radhifan Syauqi (Fisarrearch, 2021)
Aims of this research are to Analysis of the Effects of Reprimand, Forced Letters and Administrative Sanctions on Payment of Tax Arrears (Case Study in Medan Belawan Tax Office). This study aims to find out and analyze the level of effectiveness of tax collection with letters of reprimand, forced letters an administrative sanctions in KPP Medan Belawan in order to increase tax revenues. And to find out how much the contribution of tax collection with letters of reprimand, forced letters and administrative sanctions against the payment of tax arrears on the KPP Medan Belawan. This research method uses descriptive analysis, effectiveness ratio, and contribution ratio with data collection techniques in the form of observation and interviews, and documentation. The results of this study indicate that the application of tax collection with a letter of reprimand forced letters, administrative sanctions against tax receipts at the Medan Belawan KPP proved to be quite effective. Whereas, for the contribution to tax disbursement is still very lacking, so there are still many improvements needed in terms of collecting the tax.